THE ROLE OF INTERNATIONAL INSTITUTIONS IN IMPLEMENTATION OF THE LAW AGAINST GROSS HUMAN RIGHTS CRIMES IN THE CONTEXT OF GENOCIDE - Nopit Ernasari; Devi Anggaeni (PT. ZILLZELL MEDIA PRIMA, 2025)
Human rights are a basic concept that recognizes the rights inherent in all human beings based on their humanity. These rights are universal and apply to all individuals at all times and in all places. These rights are irrevocable and cannot be taken away. In addition, human rights are interconnected, interdependent, and inseparable. Gross human rights crimes, such as crimes against humanity, are committed systematically and on a widespread scale with the aim of using power. These crimes are categorized as extraordinary crimes, with special characteristics and defined in laws relating to human rights courts. These crimes include crimes such as genocide and crimes against humanity. The serious problem of human rights crimes has received international attention, with the Rome Statute on the International Criminal Court dealing with these crimes. International institutions, such as the United Nations, play an important role in protecting human rights, in line with their responsibility to uphold international security and peace.